2019
DOI: 10.3390/molecules24244573
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical and Functional Characterization of M28 Aminopeptidase Protein Secreted by Acanthamoeba spp. on Host Cell Interaction

Abstract: Acanthamoeba are a free-living protozoan whose pathogenic strain can cause severe human diseases, such as granulomatous encephalitis and keratitis. As such, the pathogenic mechanism between humans and Acanthamoeba is still unknown. In our previous study, we identified the secreted Acanthamoeba M28 aminopeptidase (M28AP) and then suggested that M28AP can degrade human C3b and iC3b for inhibiting the destruction of Acanthamoeba spp. with the human immune response. We constructed the produced the recombinant M28A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For instance, previous studies have revealed that certain secreted proteins, such as aminopeptidases and exosome-like vesicles, have been identified as virulence factors in pathogenic Acanthamoeba [ 11 , 12 ]. These proteins, when released by Acanthamoeba , disrupt epithelial cells and induce apoptosis [ 13 ]. The extracellular proteins secreted by Acanthamoeba not only affect the amoeba itself but also influence the microbiota in the microenvironment [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous studies have revealed that certain secreted proteins, such as aminopeptidases and exosome-like vesicles, have been identified as virulence factors in pathogenic Acanthamoeba [ 11 , 12 ]. These proteins, when released by Acanthamoeba , disrupt epithelial cells and induce apoptosis [ 13 ]. The extracellular proteins secreted by Acanthamoeba not only affect the amoeba itself but also influence the microbiota in the microenvironment [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, Giemsa staining of CSF confirmed the presence of Acanthamoeba cysts. This led to the identification of congenital lumbar sinus as a possible access point for Acanthamoeba infection 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…This led to the identification of congenital lumbar sinus as a possible access point for Acanthamoeba infection. 8,9 F I G U R E 1 Inverted light microscopic images of (A) ×200 magnification of Acanthamoeba cysts, while (B) ×400 magnification of trophozoites. The scale bar represents 2 µm [Color figure can be viewed at wileyonlinelibrary.com] Over the last few decades, there has been an increase in the number of infections due to Acanthamoeba.…”
Section: Introductionmentioning
confidence: 99%